Extraction and characterization of pectins from primary cell walls of edible açaí (Euterpe oleraceae) berries, fruits of a monocotyledon palm. (20th February 2017) - Cantu-Jungles, Thaisa Moro; Iacomini, Marcello; Cipriani, Thales R.; Cordeiro, Lucimara M.C.
Highlights: Structural diversity of pectins in açaí primary cell walls has been evaluated. A highly methoxylated homogalacturonan with a DM of 88% and Mw of 22 kDa was found. An AG-II with mainly 6- O - and 3, 6- O -Gal p units in the backbone was also isolated. This study brings new insights into the polysaccharide composition of palms primary cell walls. Abstract: Açaí berries ( Euterpe oleracea ) are greatly consumed in Brazil and exported to other countries as a nutritional supplement, due to health benefits attributed to its consumption. However, the complete chemical structure of bioactive polysaccharides was not fully elucidated yet. In this work, we characterize pectic polysaccharides from açaí berries through monosaccharide composition, HPSEC, methylation and 13 C and 1 H/ 13 C HSQC-DEPT-NMR analyses. A highly methoxylated homogalacturonan with a DM of 88% and Mw of 22 kDa together with small amounts of a mannoglucan were found. Moreover, a type II arabinogalactan (Mw = 45 kDa) containing a backbone with high portions of 6- O -linked and 3, 6- O -linked Gal p chains rather than 3- O -linked Gal p was also isolated and structurally characterized. The type II arabinogalactan was found as a side chain of a type I rhamnogalacturonan. These findings contribute to correlate the fine chemical structure with the previously reported action of açaí polysaccharides on innate immune response. Moreover, from the taxonomic point of view, the results bring new information about polysaccharide composition of primary cell walls of palms (Arecaceae), that despite being commelinid monocots, have a distinct cell wall composition.